Biologically Active Substances of Siberian Medical Plants in Functional Wgey-Based Drinks - Ivanova S.; Milenteva I.; Asyakina L.; Lukin A.; Kriger O.; Petrov A. (Техника и технология пищевых производств)
The use of infusions and extracts from domestic plant materials is a promising direction in the development of functional beverages since they contain a wide range of substances of various pharmacological properties. Drinks fortified with physiologically active natural components maintain a certain level of this content in human body. They can have a healing or prophylactic effect. However, there is a lack of technologies for the effective production of biologically active substances from plant materials. Moreover, the development of cultivated botanical medicinal plant species remains quite poor. The present study features the qualitative and quantitative composition of biologically active substances of medicinal plants that are endemics of Siberia. They are Rhodiola rosea (Rhodiola rosea L.) and maral root (Rhaponticum carthamoides). The paper introduces a method for increasing their biosynthetic activity. An experiment helped to select a composition of the nutrient medium for the cultivation of callus cultures of Rhodiola rosea (Rhodiola rosea L.) and maral root (Rhaponticum carthamoides) in vitro, which contributed to an increase in the biosynthesis of biologically active substances. For callus cultures of Rhodiola Rosea (line R.r-1k) the following composition was used: mineral base – MS; sucrose – 30 g; inositol – 100 mg; thiamine – 1.0 mg; pyridoxine – 1.0 mg; Ca-panthetonate – 10 mg; kinetin – 0.05 g; naphthyl acetic acid – 0.1 g; 2.4-D – 0.5. For callus cultures of maral root (line R.c -2k): mineral base – SH; sucrose – 30 g; inositol – 100 mg; thiamine – 5.0 mg; pyridoxine – 0.5 mg; nicotinic acid – 5.0 mg; kinetin – 0.1 g; indoleacetic acid – 1.0 g. The authors developed a technology for the production of functional whey-based tonic drink fortified with extract of carotenoids isolated from the fruits of mountain ash and the extract of biologically active substances Rhodiola rosea and maral root. The presence of biologically active substances in the plant and medicinal raw materials gives the drink antioxidant and bactericidal properties, as well as helps to raise the overall state of the organizm and strengthen the immune system.